2022
DOI: 10.3390/jof8111129
|View full text |Cite
|
Sign up to set email alerts
|

Waterless Dyeing and In Vitro Toxicological Properties of Biocolorants from Cortinarius sanguineus

Abstract: As a part of an ongoing interest in identifying environmentally friendly alternatives to synthetic dyes and in using liquid CO2 as a waterless medium for applying the resulting colorants to textiles, our attention turned to yellow-to-red biocolorants produced by Cortinarius sanguineus fungus. The three principal target anthraquinone colorants (emodin, dermocybin, and dermorubin) were isolated from the fungal bodies using a liquid–liquid separation method and characterized using 700 MHz NMR and high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Previously, we have studied that they can be utilized in supercritical CO 2 dyeing that does not involve the use of fresh water and that they exhibit low toxicity. 5 In the present work, we studied the previously unknown metabolic properties of dermocybin and dermorubin. We found that dermorubin was not metabolized in in vitro incubation system by human liver microsomal or cytosolic fractions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have studied that they can be utilized in supercritical CO 2 dyeing that does not involve the use of fresh water and that they exhibit low toxicity. 5 In the present work, we studied the previously unknown metabolic properties of dermocybin and dermorubin. We found that dermorubin was not metabolized in in vitro incubation system by human liver microsomal or cytosolic fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether this data contributes the previous in vitro safety data on dermorubin and dermocybin. 5 European chemical legislation requires in vivo toxicity testing for chemical substances such as biocolourants when entering the market and their production exceeds certain limit. Consequently, it is important to know the metabolism of xenobiotics in different species to increase the reliability of the toxicity assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations